2011
DOI: 10.1089/jwh.2010.2104
|View full text |Cite
|
Sign up to set email alerts
|

Race and Sexually Transmitted Diseases in Women With and Without Borderline Personality Disorder

Abstract: Background: The purpose of this study was to examine the history of sexually transmitted diseases (STDs) among women with borderline personality disorder (BPD) with and without a lifetime substance use disorder (SUD) and to compare their histories to those of a group of women with a current nonpsychotic axis I disorder. Methods: Two-hundred fifteen women completed the Structured Clinical Interview for DSM-IV Axis I diagnoses (SCID-I), Structured Interview for DSM-IV Personality for Axis II diagnoses (SIDP-IV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
(49 reference statements)
3
8
0
1
Order By: Relevance
“…In our sample, those with elevated BPD symptom severity were more likely to report sex with non-monogamous partners and with those who sell sex. Just one other study examined BPD and high-risk sexual partners, but found only women with both BPD and SUD reported higher prevalence of risky sexual partners [15]. We found BPD was associated with self-reported previous STI, as have others [15], and that biologically-confirmed chlamydial infection demonstrated a similar relationship.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In our sample, those with elevated BPD symptom severity were more likely to report sex with non-monogamous partners and with those who sell sex. Just one other study examined BPD and high-risk sexual partners, but found only women with both BPD and SUD reported higher prevalence of risky sexual partners [15]. We found BPD was associated with self-reported previous STI, as have others [15], and that biologically-confirmed chlamydial infection demonstrated a similar relationship.…”
Section: Discussionsupporting
confidence: 73%
“…Just one other study examined BPD and high-risk sexual partners, but found only women with both BPD and SUD reported higher prevalence of risky sexual partners [15]. We found BPD was associated with self-reported previous STI, as have others [15], and that biologically-confirmed chlamydial infection demonstrated a similar relationship. However, our small sample with a low prevalence of infection was not powered to detect statistically significant differences in biologically assessed STI, though we hypothesize associations would be similar and significant in a larger sample.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The combination of emotion and behavioral dysregulation experienced by women with BPD may place them at greater risk of unplanned pregnancies. Although there are no studies of pregnancies or births in women with BPD, studies of sexually transmitted disease (STD) in women with BPD suggest that they may be more likely to have early and unprotected sexual intercourse than women without SMI (Chen et al, 2007) and women with other mental illness (De Genna et al, 2011). Greater sexual impulsivity, higher prevalence of sexual abuse history (Bradley, Jenei, & Westen, 2005) and comorbid substance use disorders (SUDs) may all contribute to a higher risk of unplanned pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no studies have examined pregnancy or pregnancy outcomes in women with and without BPD. Based on previous findings that BPD severity predicts risky sexual behavior and STDs (Chen et al, 2007; De Genna et al, 2011) we hypothesized that 1) women with more BPD symptoms (greater symptom severity) have had a greater number of teenage pregnancies, unplanned pregnancies, abortions, and live births when compared to women with Axis I psychiatric disorders who do not have many BPD symptoms; 2) women with greater BPD symptom severity have had more live births than women with Axis I disorders, because of the association between teenage pregnancies and higher fertility (Guzzo & Furstenberg, 2007). …”
Section: Introductionmentioning
confidence: 99%